Shallow infaunal responses to the Deepwater Horizon event: Implications for studying future oil spills - Berke, Sarah K.; Dorgan, Kelly M.; Kiskaddon, Erin; Bell, Susan; Gadeken, Kara; Clemo, William C.; Keller, Erin L.; Caffray, Theresa (Frontiers in Environmental Science, 2022)
Infaunal sedimentary communities underpin marine ecosystems worldwide. Understanding how disturbances such as oil spills influence infauna is therefore important, especially given that oil can be trapped in sediments for years or even decades. The 2010 Deepwater Horizon (DWH) event was the largest marine oil spill in United States history, impacting habitats throughout the Northern Gulf of Mexico. We investigated infaunal community structure at two shallow sites in the Chandeleur Islands, LA, USA, over a two-year period from 2015-2016 (5-6 years post-spill). One site was moderately contaminated with oil from the DWH spill, while the other was only lightly contaminated. Both sites featured patchy Ruppia seagrass meadows, allowing us to compare infaunal communities between sites for seagrass versus unvegetated sediment. The moderately-oiled site featured a significantly different community than that of the lightly oiled site; these differences were driven by altered abundance of key taxa, with some taxa being less abundant at the moderately oiled site but others more abundant. During our second year of sampling, a crude oil slick moved transiently through the moderately-oiled site, allowing us to directly observe responses to an acute re-oiling event. Virtually every taxonomic and community-level metric declined during the re-oiling, with effects more pronounced in seagrass beds than in unvegetated sediment. The sole exception was the snail, Neritina usnea, which we found exclusively at the more-oiled site. Our observations suggest that oil responses are driven more by key taxa than by entire guilds responding together. By identifying the families and genera that showed the largest signal at this pair of sites, we can begin laying groundwork for understanding which benthic taxa are most likely to be impacted by oil spills, both in the immediate aftermath of a spill and through longer-term contamination. While more studies will certainly be needed, this contribution is a step towards developing clear a priori hypotheses that can inform future oil-spill work. Such hypotheses would help to focus future sampling efforts, allowing resources to be directed towards those taxa that are most likely to be responding, and which are potential bio-indicators of oil exposure.